Solvent- and metal-free hydroboration of alkynes under microwave irradiation. Issue 11 (12th March 2020) - Gioia, Bruna; Arnaud, Alexandre; Radix, Sylvie; Walchshofer, Nadia; Doléans-Jordheim, Anne; Rocheblave, Luc
Graphical abstract: Abstract: Boronic esters are versatile building blocks extensively used in organic chemistry and essential to a variety of coupling reactions. In this work, the hydroboration reactions of alkynes were performed without metal catalysts using concomitant microwave irradiation that allowed a significantly reduced reaction time. Another interesting outcome of this study was that the reaction could be carried out under solvent-free conditions, highlighting the environmentally-friendly nature of our method. A wide scope of aryl- and alkylboronic acid pinacol esters were easily synthesized from the corresponding alkynes.